2009
DOI: 10.1111/j.1537-2995.2008.02022.x
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of an index of global oxygenation for guiding red blood cell transfusion in cardiac surgery

Abstract: If a normal O2ER in anemic patients with no evidence of organ dysfunction indicates adequate tissue oxygen delivery, then our findings suggest that incorporating O2ER into the transfusion decision will substantially reduce post-cardiac surgery RBC transfusions by allowing us to safely avoid transfusing this group of patients. Future studies are needed to assess the validity of this conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 22 publications
3
32
0
2
Order By: Relevance
“…Bu nedenle O 2 ER'in % 50'yi aşması bir transfüzyon kriteri olarak kabul edilebilir. Kardiyak cerrahide KPB sonrasında transfüzyon kararı verilirken O 2 ER değerinin de dikkate alınmasının kan kullanımını azalttığı ileri sürülmüştür (83) . Bu nedenle özellikle sorunlu hastalarda O 2 ER, transfüzyon kararı vermek için Hb düzeyinden daha güvenilir bir kriter olabilir.…”
Section: Fizyolojik Kriterlerunclassified
“…Bu nedenle O 2 ER'in % 50'yi aşması bir transfüzyon kriteri olarak kabul edilebilir. Kardiyak cerrahide KPB sonrasında transfüzyon kararı verilirken O 2 ER değerinin de dikkate alınmasının kan kullanımını azalttığı ileri sürülmüştür (83) . Bu nedenle özellikle sorunlu hastalarda O 2 ER, transfüzyon kararı vermek için Hb düzeyinden daha güvenilir bir kriter olabilir.…”
Section: Fizyolojik Kriterlerunclassified
“…(31,33,34) When anaemia results in DO2 reduction, ERO2 of 50% represents an indirect indicator of tissue oxygen deficit and may be used as a transfusion trigger. (24) Studies that compared ScVO2 and SVO2 in various clinical situations have still not provided reliable answers on the question of whether or not both of these parameters can be used for the purpose of triggering transfusion therapy. As a result of blood flow redistribution, regional impairment of tissue oxygenation and microcirculation in critically ill patients, the various outcomes of these studies are often inconclusive.…”
Section: Global Oxygenation Param-eters In Critical Illnessmentioning
confidence: 99%
“…Keeping in mind the risks from pulmonary artery catheterisation, the use of these parameters in everyday clinical practice may be difficult. (20)(21)(22)(23)(24)(25)(26) Considering the fact that most critically ill patients in medical or surgical ICUs do not have a pulmonary artery catheter inserted, or it is inserted for a short period of time, a question can be raised whether ScVO2 and ScVO2 derived ERO2 may be used as relevant transfusion indicators. SVO2 reflects the relation between DO2 and VO2 in the upper and lower parts of the body and the heart.…”
Section: Global Oxygenation Param-eters In Critical Illnessmentioning
confidence: 99%
“…This threshold might be used to consider the transfusion of RBC. In practice, a small observational study in cardiac surgery patients suggested less frequent and more appropriate blood utilization when adding O 2 ER as a guide for transfusions [54].…”
Section: Complications Of Blood Transfusions In Surgical Patientsmentioning
confidence: 99%
“…The enthusiasm for the use of EPO, however, has been curbed by inconsistent success with EPO [59], and by serious concerns about the adverse effects of EPO. These include an increased risk for thrombosis and stroke [54], and a potentially direct stimulating effect of EPO on tumor cell growth [60,61].…”
Section: Preoperative Optimization Of Patientsmentioning
confidence: 99%